Application development on Android phone approve : agreement assistant for today’s business - Rima Raksanegara (2015)
The number of new businesses has been continuously growing and technology has played a very important role in today’s business environment. Due to this phenomenon, there is a need for closing a business deal faster. Together with the increasing awareness of greater involvement of mobile devices in business operation, a number of applications have been developed and offered to fulfill this need. However, this phenomenon triggers negative impacts on the security of business processes, such as fraud in online transactions, and yet not many of those introduced applications have taken security into consideration. Looking at this challenge, the author decided to develop an Android application, namely Approve, to help speed up the business process as well as increase the level of its security with a new innovation in creating, managing, and signing contracts mobile. With the utilization of available Android sensors and public APIs, Approve can be used as a platform for people to ease their business operation. The application facilitates a simple but secured procedure to create, reject, and approve a contract. With the utilization of video capture on Android phone, a new procedure in signing a contract remotely is offered. Signature verification feature is offered by leveraging public third-party Face Recognition API. The registered signature (the user’s portrait) is matched against the signature attached on the contract. Thereafter, a one-time password (OTP) is delivered to user’s mobile via SMS as additional confirmation of contract approval. The project deliverables have been successfully fulfilled, while still giving ample room for the application to be extended. Developed with a strong motivation to make a useful and novel application in the market, Approve is expected to be able to provide excellent and helpful functionalities to its target users.